Serial Entertainment: A Content Analysis of 35 Years of Serial Murder in Film. Issue 4 (November 2019) - Call, Corey
Serial murder is a rare phenomenon, yet an incredibly popular topic as evidenced by the availability of various types of entertainment media about serial murder. The present study provides a content analysis of serial murder in film utilizing 50 randomly selected films covering a 35-year period (1980-2015). Data were coded for 53 fictional killers and 362 victims to generate profiles of the typical serial killer and their victims in film. The results are discussed in relation to real-world data on serial murder to describe the accuracies and inaccuracies of the portrayal of serial murder in film.